Mff‐Dependent Mitochondrial Fission Contributes to the Pathogenesis of Cardiac Microvasculature Ischemia/Reperfusion Injury via Induction of mROS‐Mediated Cardiolipin Oxidation and HK2/VDAC1 Disassociation‐Involved mPTP Opening. Issue 3 (13th March 2017) - Zhou, Hao; Hu, Shunying; Jin, Qinhua; Shi, Chen; Zhang, Ying; Zhu, Pingjun; Ma, Qiang; Tian, Feng; Chen, Yundai
Abstract : Background: The cardiac microvascular system ischemia/reperfusion injury following percutaneous coronary intervention is a clinical thorny problem. This study explores the mechanisms by which ischemia/reperfusion injury induces cardiac microcirculation collapse. Methods and Results: In wild‐type mice, mitochondrial fission factor (Mff) expression increased in response to acute microvascular ischemia/reperfusion injury. Compared with wild‐type mice, homozygous Mff‐deficient (Mff gt ) mice exhibited a smaller infarcted area, restored cardiac function, improved blood flow, and reduced microcirculation perfusion defects. Histopathology analysis demonstrated that cardiac microcirculation endothelial cells (CMECs) in Mff gt mice had an intact endothelial barrier, recovered phospho‐endothelial nitric oxide synthase production, opened lumen, undivided mitochondrial structures, and less CMEC death. In vitro, Mff‐deficient CMECs (derived from Mff gt mice or Mff small interfering RNA–treated) demonstrated less mitochondrial fission and mitochondrial‐dependent apoptosis compared with cells derived from wild‐type mice. The loss of Mff inhibited mitochondrial permeability transition pore opening via blocking the oligomerization of voltage‐dependent anion channel 1 and subsequent hexokinase 2 separation from mitochondria. Moreover, Mff deficiency reduced the cyt‐c leakage into the cytoplasm by alleviating cardiolipin oxidation resulting from damage to the electron transport chain complexes and mitochondrial reactive oxygen species overproduction. Conclusions: This evidence clearly illustrates that microcirculatory ischemia/reperfusion injury can be attributed to Mff‐dependent mitochondrial fission via voltage‐dependent anion channel 1/hexokinase 2–mediated mitochondrial permeability transition pore opening and mitochondrial reactive oxygen species/cardiolipin involved cyt‐c release.